2001
DOI: 10.1071/ah010022
|View full text |Cite
|
Sign up to set email alerts
|

Organisational governance structures in allied health services:A decade of change

Abstract: A ten year review of developments in the organisation and management of allied health services in Australian acute care public hospitals reveals a steady transformation away from a medically managed universal model towards more complex and contested models of governance. This article revisits early observations about the reorganisation of allied health services and presents more recent research findings to guide managerial decision-making about restructuring the diverse disciplines that constitute allied healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 13 publications
0
46
0
Order By: Relevance
“…Despite disciplinary differences, however, practitioners tend to cite factors such as the increasing value of community-based service delivery, the reduction of therapist control and a corresponding increase in client control, and sociopolitical determinants of health, for the adoption of wellness and its components [20][21][22]. As a result, allied health professionals are left to reconcile the tension created from the increasing consumer demand for wellness approaches [23] with the health and disability sectors. For instance, a recent Australian study searched for indicators of wellness and demonstrated that the rhetoric of wellness is drawn upon heavily within the policy and procedure documents of major childhood disability services providing allied health services within Australia [24].…”
Section: Current Status Of Wellness In Health and Disability Servicesmentioning
confidence: 99%
“…Despite disciplinary differences, however, practitioners tend to cite factors such as the increasing value of community-based service delivery, the reduction of therapist control and a corresponding increase in client control, and sociopolitical determinants of health, for the adoption of wellness and its components [20][21][22]. As a result, allied health professionals are left to reconcile the tension created from the increasing consumer demand for wellness approaches [23] with the health and disability sectors. For instance, a recent Australian study searched for indicators of wellness and demonstrated that the rhetoric of wellness is drawn upon heavily within the policy and procedure documents of major childhood disability services providing allied health services within Australia [24].…”
Section: Current Status Of Wellness In Health and Disability Servicesmentioning
confidence: 99%
“…Sociologists have also focused on the well-being of health workers when their work environments are privatised or corporatised (e.g., Duff and Larsen 2003;Mahony 2005), and there has been a documenting of the deteriorating physical health of the broader population as a consequence of the privatisation of essential services, including water (e.g., Whelan and White 2005). There has also been a small amount of work on the effects of privatisation on health and medical workers, particularly with regard to the issue of professional autonomy and the potential for marketisation to undermine medical dominance (e.g., Benoit et al 2010;Boyce 2001;Lewis et al 2003;Lewis and Marjoribanks 2003).…”
Section: Kevin Whitementioning
confidence: 98%
“…In contrast to the organisational structure in this first case, the second case operated within a divisional structure characterized by integrated decentralisation (Boyce, 2001). This structure builds on the benefits of a division of allied health model and the programme management-based unit dispersement approach.…”
mentioning
confidence: 97%